2001
DOI: 10.1021/la010848g
|View full text |Cite
|
Sign up to set email alerts
|

Buildup Mechanism for Poly(l-lysine)/Hyaluronic Acid Films onto a Solid Surface

Abstract: The formation of a new kind of biocompatible film based on poly(L-lysine) and hyaluronic acid (PLL/HA) by alternate deposition of PLL and HA was investigated. Optical waveguide lightmode spectroscopy, streaming potential measurements, atomic force microscopy, and quartz crystal microbalance (QCM) were used to analyze the different aspects of the buildup process such as the deposited mass after each new polyelectrolyte adsorption, the overall surface charge of the film, and its morphology. As for "conventional"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

71
850
4
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 666 publications
(927 citation statements)
references
References 59 publications
71
850
4
2
Order By: Relevance
“…Finally, when the next Au NPs layer is added (Figure 5g), both structural elements coalesce into homogeneous regions, and neither small spheroids nor ordered structures of the polymer are observed. At this point, the film has developed a dense, well-packed structure, very much in a manner observed previously in PEMUs 44,45 as well as in dendrimers/Ag NPs. 52 Wang et al 53 have also observed in poly s-119/Au NPs multilayers a uniform coverage over areas macroscopic compared with the particle size when 20 bilayers have been deposited.…”
Section: Multilayer Characterizationsupporting
confidence: 67%
“…Finally, when the next Au NPs layer is added (Figure 5g), both structural elements coalesce into homogeneous regions, and neither small spheroids nor ordered structures of the polymer are observed. At this point, the film has developed a dense, well-packed structure, very much in a manner observed previously in PEMUs 44,45 as well as in dendrimers/Ag NPs. 52 Wang et al 53 have also observed in poly s-119/Au NPs multilayers a uniform coverage over areas macroscopic compared with the particle size when 20 bilayers have been deposited.…”
Section: Multilayer Characterizationsupporting
confidence: 67%
“…This is somewhat unexpected since the surface features of films that are prone to change (dynamic PECs) would be expected to lead to smooth films after the deposition of a few layers due to the action of surface tension. This smoothing of surfaces has been previously observed with LbL-films composed of hyaluronic acid and poly(L-lysine) [57], and smooth films have also been observed, for example, with soft polyelectrolytes such as poly(acrylic acid) and poly(allyl amine). The control of the feature size of surface patterns is an interesting new aspect in the field of PEMs because this technique is easily applicable to large surface areas for which patterning is difficult to obtain with low cost methods.…”
Section: Discussionsupporting
confidence: 74%
“…the material adsorbed on the electrode increases more than linearly with the number of deposited layers. This nonlinear or exponential growth of the film was also observed previously in the formation of PLL/PGA films on other substrates [13,18,19] and in films comprising PLL or PGA, for example, PLL/hyaluronic acid [20] and PGA/poly(allylamine hydrochloride) [21] multilayer films. Previous studies on polyelectrolyte LbL multilayer films have demonstrated that the growth of the multilayer film is entropy driven and an endothermic complexation process of PLL/PGA corresponds to the exponential growth of the film [22].…”
Section: Pll/pga Multilayer Film Assemblysupporting
confidence: 82%